PENGARUH BRAND EQUITY DAN CUSTOMER EXPERIENCE TERHADAP CUSTOMER LOYALTY DI WAROENG STEAK AND SHAKE MELATI PEKANBARU - Yuly Meta Agustin Pasaribu; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine the effect of Brand Equity and Customer Experience on Customer Loyalty in Waroeng Steak and Shake Melati Pekanbaru. Where two independent variables and one dependent variable, brand equity and customer experience as independent variable and customer loyalty act as dependent variable. The population in this research is consumers Waroeng Steak and Shake Melati Pekanbaru with sampling amounted to 100 people calculated by using Slovin formula. The sampling technique is done by purposive sampling. Collecting research data in the form of primary data by using questionnaires as research instruments, data analysis used is to use multiple linear regression analysis with the help of SPSS program. From the results of tests conducted show that brand equity and customer experience have a positive and significant impact on customer loyalty. Where the value of coefficient of determination (R2) shows that the variable brand equity and customer experience contribute to customer loyalty variable of 50.7% while the rest of 49.3% influenced by other variables not included in this study.Keywords: brand equity, customer experience, and customer loyalty.